Dynamics of mononychellus tanajoa (acari: tetranychidae) in africa: seasonal factors affecting phenology and abundance - Yaninek, J.; Herren, H.R.; Gutierrez, A.P. (1989)
Populations of Mononychellus tanajoa (Bondar) increased on new leaf growth of cassava, Manihot esculenta Crantz, during the early dry season, averaging 20–200 active mites per leaf depending on plant age, leaf age, and cultivar. Mite populations declined later in the dry season, when severe defoliation and reduced leaf production followed prolonged drought. Early rains resulted in a flush of new foliage that supported an increase in mite numbers, but rainfall drove mite populations to less than one individual per leaf several months into the wet season. Throughout the growing season, mite age structure was relatively constant within, but varied between, strata of the canopy. Differences between strata were related to the age of the foliage. These results suggest that the availability of new foliage and the presence of rainfall are the primary factors limiting M. tanajoa populations in Africa.